The Ganymede Laser Altimeter (GALA) for the Jupiter Icy Moons Explorer (JUICE): Mission, science, and instrumentation of its receiver modules. Issue 5 (1st March 2022) - Enya, Keigo; Kobayashi, Masanori; Kimura, Jun; Araki, Hiroshi; Namiki, Noriyuki; Noda, Hirotomo; Kashima, Shingo; Oshigami, Shoko; Ishibashi, Ko; Yamawaki, T.; Tohara, Kazuyuki; Saito, Yoshifumi; et al.
Abstract: The Jupiter Icy Moons Explorer (JUICE) is a science mission led by the European Space Agency, being developed for launch in 2023. The Ganymede Laser Altimeter (GALA) is an instrument onboard JUICE, whose main scientific goals are to understand ice tectonics based on topographic data, the subsurface structure by measuring tidal response, and small-scale roughness and albedo of the surface. In addition, from the perspective of astrobiology, it is imperative to study the subsurface ocean scientifically. The development of GALA has proceeded through an international collaboration between Germany (the lead), Japan, Switzerland, and Spain. Within this framework, the Japanese team (GALA-J) is responsible for developing three receiver modules: the Backend Optics (BEO), the Focal Plane Assembly (FPA), and the Analog Electronics Module (AEM). Like the German team, GALA-J also developed software to simulate the performance of the entire GALA system (performance model). In July 2020, the Proto-Flight Models of BEO, FPA, and AEM were delivered from Japan to Germany. This paper presents an overview of JUICE/GALA and its scientific objectives and describes the instrumentation, mainly focusing on Japan's contribution.